2005
DOI: 10.1302/0301-620x.87b8.15772
|View full text |Cite
|
Sign up to set email alerts
|

A hydroxyapatite-coated total knee replacement

Abstract: We prospectively reviewed 1000 consecutive patients who underwent a cementless, hydroxyapatite-coated, stemless, total knee replacement over a period of nine years. Regular post-operative clinical follow-up was performed using the Knee Society score. The mean pre-operative score was 96, improving to 182 and 180 at five and ten years, respectively. To date, there have been seven (0.5%) cases which required revision, primarily for septic loosening (four cases), with low rates of other post-operative complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 22 publications
(25 reference statements)
4
31
0
Order By: Relevance
“…Functional results and survivorship of HA-coated implants are comparable to cemented implants. [33][34][35][36] In a study of 81 patients randomized to HA-coated or cemented implants, Beaupre et al 33 showed no differences in function, radiographic findings, or complications at 5 years postoperatively. Similarly, Cossetto and Gouda 31 reported a survivorship of 98.85% and bony ingrowth in all but one of their cementless tibial implants with HA overcoating.…”
Section: New Perspectivesmentioning
confidence: 99%
“…Functional results and survivorship of HA-coated implants are comparable to cemented implants. [33][34][35][36] In a study of 81 patients randomized to HA-coated or cemented implants, Beaupre et al 33 showed no differences in function, radiographic findings, or complications at 5 years postoperatively. Similarly, Cossetto and Gouda 31 reported a survivorship of 98.85% and bony ingrowth in all but one of their cementless tibial implants with HA overcoating.…”
Section: New Perspectivesmentioning
confidence: 99%
“…10 Currently, Ͼ95% survivorship can be expected with both cemented and cementless primary TKA at long-term follow-up. 1,14,18,19,24,41,51 Therefore, although these early results are encouraging, longer-term follow-up is necessary to validate the efficacy of this prosthesis.…”
Section: D 3ementioning
confidence: 99%
“…[17][18][19][20] Despite these early problems, innovations in biomaterials and implant design have led to improved osseointegration and implant fixation, which could potentially improve cementless TKA long-term survivorship. 14,16,21,22 With newer implant designs, the optimal fixation for TKA components remains debatable, and therefore, the purpose of this meta-analysis was to assess the evidence supporting the use of cementless versus cemented TKAs. The specific aims were to evaluate (1) all-cause survivorship, (2)…”
mentioning
confidence: 99%